Hospital Building Value Engineering Strategy in Accordance with Building Technical Standards - Joko Riyanto; Slamet Imam Wahyudi; Kartono Wibowo (Advance Sustainable Science Engineering and Technology, 2026)
This study developed a Value Engineering strategy for hospital buildings in accordance with Indonesian technical standards, namely Government Regulation No. 16, Minister of Health Regulation No. 40, and Minister of Public Works and Public Housing Regulation No. 21 concerning Green Building Performance Assessment. The purpose of this study was to determine design-appropriate variable criteria and formulate improvement strategies for variables that did not meet the requirements. A quantitative methodology was applied using the Likert strategy, validity and reliability tests (Guttman Split-Half), and mean value analysis. The results showed 16 variables valid, reliable, and feasible indicators (mean 0.92–0.99). Improvement strategies were applied to 16 variables, including additional innovations of 9 variables. The developed Value Engineering strategy is statistically significant and can be used as a reference for hospital planning decision-making, contributing to improved efficiency, sustainability, and quality of hospital buildings in Indonesia.